2018
DOI: 10.1016/j.seizure.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical derangements related to metabolic syndrome in epileptic patients on treatment with valproic acid

Abstract: VPA treatment increased the risk factors for the development of metabolic syndrome such as hyperinsulinemia, insulin resistance and oxidative stress. However VPA treatment corrected the dyslipidemia of epileptic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…In our study, the HsCRP of both participated cases and controls was measured to evaluate possible in ammatory effects of AEDs, but our ndings showed that there was no signi cant difference in the levels of HsCRP between the VPA-treated group, the CBZ-treated group, and the controls. Although our result was supported by Nisha et al [48] Using the various indexes for evaluation of MetS and IR in epileptic patients is the strength of our study which is more than in other published studies. This study has some limitations, including limited sample size, lack of information on patients' MetS components before taking AEDs and also unmatched age of CBZ-treated and VPA-treated cases which was due to the nature of study in which CBZ usually should be prescribed for adult epileptics with partial epilepsy and VPA for younger subjects with generalized epilepsy.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In our study, the HsCRP of both participated cases and controls was measured to evaluate possible in ammatory effects of AEDs, but our ndings showed that there was no signi cant difference in the levels of HsCRP between the VPA-treated group, the CBZ-treated group, and the controls. Although our result was supported by Nisha et al [48] Using the various indexes for evaluation of MetS and IR in epileptic patients is the strength of our study which is more than in other published studies. This study has some limitations, including limited sample size, lack of information on patients' MetS components before taking AEDs and also unmatched age of CBZ-treated and VPA-treated cases which was due to the nature of study in which CBZ usually should be prescribed for adult epileptics with partial epilepsy and VPA for younger subjects with generalized epilepsy.…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, CBZ therapy showed signi cant correlation with IR risk based on HOMA index only. Most studies have used the HOMA index, and they have reported signi cantly increased values of IR in VPA-treated cases [1,2,36,48]. However, Naja et al [19] studied the VPA-treated Iranian patients and they reported that there were normal values of insulin and no evidence of IR in VPA-treated as case and CBZ -treated as controls and this nding has also been supported by a study conducted by Kwan et al [49].…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, treatment with VPA predisposed obese children with idiopathic epilepsy to insulin resistance and lower adiponectin levels compared to age and gender matched obese controls [88]. VPA also induced hypoadiponectinemia and insulin resistance in previously untreated people with epilepsy [89,90]. Other studies, however, have found non-significant increases in adiponectin levels after VPA treatment [91,92].…”
Section: 6mentioning
confidence: 99%
“…Proposed Mechanisms for Development of T2DM in People with Epilepsy One possible mechanism that we propose for the development of T2DM in people with epilepsy is that mitochondrial dysfunction [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] and adiponectin deficiency [83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102] predispose people to epilepsy, obesity, and diabetes. The same biological drivers underlie each of these three conditions due to the systemic nature of both these drivers and the conditions.…”
Section: 7mentioning
confidence: 99%
“…54 Oxidative stress parameters were elevated in VPA-treated patients with epilepsy as compared with the nontreated control. 55 The reactive oxygen species (ROS) production can cause direct damage to cellular DNA, protein, lipids, and can alter normal cell signaling pathways. 56 The VPA has been shown to increase ROS production and induce apoptosis in several cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%